EFFECT OF FOLIAR APPLICATION OF NITROGEN ON GRAIN YIELD AND IT’S COMPONENT IN SORGHUM - & et al., Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out at the experimental farm. College of Agriculture, Anbar University (in replace location Abu – Gharib), during the spring and autumn season of 2015. The main objective was to find out the effect of nitrogen concentration (0, 1.5, 3.0, and, 4.5) g.L -1 and three stages of foliar application (vegetative growth, booting and 25% flowering) on grain yield and it’s major components of sorghum cv. Bohooth. 70 The layout of the experiment was a split plot in a randomized complete block design with three replications. nitrogen concentration were used as main plots, while stages of foliar of nitrogen were used as sub-plots. Results, showed that in both season addition of nitrogen at a conc more than 1.5 g.L -1 (3.0, 4.5) resulted in a significant increment in mean of plant height, leaf area grain weight. head -1, No. of grain .head -1, grain yield and biological yield. while weight of 1000 grain and harvest index were only significantly influenced in autumn seasons. In spring and autumn season highest grain yield (2.548, 4.111) t. ha -1 was obtained when plants sprayed with 4.5 g. L -1. the of increment in grain yield when N spray at conc (1.5, 3, 4.5) g.L-1 compare with control treatment (13.6%, 40.8%, 43.9%) and (17.47%, 42%, 54.8%) for spring and autumn season respectively. Foliar application of N at different stages of growth had only significant effect on plant height and leaf area in autumn season and biological yield in both season ,when foliar application at vegetative growth gave highest mean for these traits .